Analysis of International Trade Liberalisation In The Perspective of Islamic Economic Law Justice - Royani, Royani; Setiawan, Iwan (Asian Journal of Social and Humanities, 2024)
International trade is a process of exchange based on the voluntary will of each country. The motive is to gain from trade. International trade and Islamic economics are two things that overlap in influencing the economic growth of a country. In the perspective of Islamic economics, these two aspects have an important role in achieving the goal of falah (prosperity) in this world and the hereafter. This research examines the effect of international trade and the shariah economy on economic growth in the perspective of Islamic economics. The analysis is conducted by reviewing the concepts and principles of Islamic economics related to international trade activities and the application of the Shariah economy. The results show that international trade based on Islamic economic principles, such as justice, balance, and benefit, can make a positive contribution to economic growth. Meanwhile, the application of shariah economy that prioritises spiritual values and Islamic business ethics can create a conducive investment climate and encourage sustainable economic growth. Trade is a very important economic activity today, so there are no countries in the world that are not involved in trade, either inter-regional, inter-regional, or inter-country trade. While trade liberalisation or free trade is a condition in which a country conducts trade between countries without any barriers. This research is descriptive qualitative with literature study. Based on the above study, it can be concluded that the perspective of Islamic law related to international trade liberalisation is a liberal economic system that will lead to social inequality and can endanger the stability of economic security in accordance with the Islamic concept based on the principles of justice, honesty, recognition of performance and hard work, humanism, and non-centralisation.